Cerebral Microangiopathy in Leukoencephalopathy With Cerebral Calcifications and Cysts: A Pathological Description. (February 2021) - Helman, Guy; Viaene, Angela N.; Takanohashi, Asako; Breur, Marjolein; Berger, Rebecca; Woidill, Sarah; Cottrell, John R.; Schiffmann, Raphael; Crow, Yanick J.; Simons, Cas; Bugiani, Marianna; Vanderver, Adeline
Leukoencephalopathy with calcifications and cysts (LCC) is a neurological syndrome recently associated with pathogenic variants in SNORD118 . We report autopsy neuropathological findings from an individual with genetically confirmed LCC. Histologic studies included staining of formalin-fixed paraffin-embedded tissue sections by hematoxylin and eosin, elastic van Gieson, and luxol fast blue. Immunohistochemistry stains against glial fibrillary acidic protein, proteolipid protein, phosphorylated neurofilament, CD31, alpha-interferon, LN3, and inflammatory markers were performed. Gross examination revealed dark tan/gray appearing white matter with widespread calcifications. Microscopy revealed a diffuse destructive process due to a vasculopathy with secondary ischemic lesions and mineralization. The vasculopathy involved clustered small vessels, resembling vascular malformations, and sporadic lymphocytic infiltration of vessel walls. The white matter was also diffusely abnormal, with concurrent loss of myelin and axons, tissue rarefaction with multifocal cystic degeneration, and the presence of foamy macrophages, secondary calcifications, and astrogliosis. The midbrain, pons, and cerebellum were diffusely involved. It is not understood why variants in SNORD118 result in a disorder that predominantly causes neurological disease and significantly disrupts the cerebral vasculature. Clinical and radiological benefit was recently reported in an LCC patient treated with Bevacizumab; it is important that these patients are rapidly diagnosed and trial of this treatment modality is considered in appropriate circumstances.